2020
DOI: 10.5028/jatm.v12.1108
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Aerodynamic Characteristics of a Wing Model With RGV Winglet

Abstract: This work describes the aerodynamic characteristics of an aircraft wing model with a Rüppell’s griffon vulture (RGV)-type winglet. A computational fluid dynamics (CFD) study using ANSYS 15.0 was conducted to study the effect of the RGV winglet on a rectangular wing. The NACA 65(3)-218 wing consists of 660 mm span and 121 mm chord length where the aspect ratio is 5.45. Eight different winglet configurations have been studied. Furthermore, the study is extended to study effect of cant angle and different angles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Consequently, the development and optimization of these devices has been the subject of several studies. In a pioneering study, Krishnan et al (2020) investigated the application of a Rüppell's Griffon Vulture (RGV) type winglet to a rectangular wing. The results showed that by using an RGV winglet, there was an increase of 25% to 75% in aerodynamic efficiency compared to other types of winglet configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the development and optimization of these devices has been the subject of several studies. In a pioneering study, Krishnan et al (2020) investigated the application of a Rüppell's Griffon Vulture (RGV) type winglet to a rectangular wing. The results showed that by using an RGV winglet, there was an increase of 25% to 75% in aerodynamic efficiency compared to other types of winglet configurations.…”
Section: Introductionmentioning
confidence: 99%